2021
DOI: 10.1111/bjet.13103
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adaptivity in digital learning technologies. Modelling learning efficiency using data from an educational game

Abstract: During the last decade, many governments and ed‐tech companies have demonstrated an increased interest in digital personalised learning, which resulted in a variety of often game‐like adaptive learning environments. However, there has been limited attention for the impact of these personalised learning technologies on children's learning efficiency. Does digital personalised learning, like popular claims insist, foster learning in young children? This study attempts to empirically validate the beneficial impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(99 reference statements)
0
9
0
1
Order By: Relevance
“…This evidence can be obtained by conducting controlled designs in which the effects of personalised learning environments are contrasted with non-personalised learning environments. The study of Debeer et al (2021) empirically validated the beneficial impact of an adaptive learning game by analysing the log data from an adaptive and non-adaptive version of the Number Sense Game that trains early numerical skills. The researchers used innovative approaches to model the students' progress over time, thereby giving an indication of the students' learning efficiency.…”
Section: Methodsmentioning
confidence: 97%
“…This evidence can be obtained by conducting controlled designs in which the effects of personalised learning environments are contrasted with non-personalised learning environments. The study of Debeer et al (2021) empirically validated the beneficial impact of an adaptive learning game by analysing the log data from an adaptive and non-adaptive version of the Number Sense Game that trains early numerical skills. The researchers used innovative approaches to model the students' progress over time, thereby giving an indication of the students' learning efficiency.…”
Section: Methodsmentioning
confidence: 97%
“…One of the affordances of digital games is the opportunity to use log data as an objective performance measure for learning analytics (Shute et al, 2015) since it provides detailed information about students' learning (Debeer et al, 2021). Log data can be used to assess learning outcomes of students without needing assessments on paper (Alonso‐Fernández et al, 2019) and can give detailed insights into underlying attentional processes of the individual learner (Wang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study, Zaveri, B., et al [8] proved that learners can complete tasks quickly and recognize the usability of online learning platforms by improving interactive communication, thus enabling students to improve their learning efficiency greatly. Debeer, D., et al [9] reported that education games can improve learners' ability to adapt to learning environments and improve the learning efficiency of children.…”
Section: Literature Reviewmentioning
confidence: 99%